An open-label, acute clinical trial in adults to assess ketone levels, gastrointestinal tolerability, and sleepiness following consumption of (R)-1,3-butanediol (Avela™) - Lowder, James; Fallah, Shafagh; Venditti, Carolina; Musa-Veloso, Kathy; Kotlov, Vassili (Frontiers in Physiology, 2023)
A study was undertaken to determine the acute effects of a beverage made with Avela™, (R)-1,3-butanediol, on blood beta-hydroxybutyrate (BHB) levels (using the Keto-Mojo monitor), gastrointestinal (GI) tolerability (using the modified visual analogue scale GI Symptoms Tool), and sleepiness (using the Stanford Sleepiness Scale). Following a 12-hour overnight fast, 26 healthy adults consumed one beverage containing 11.5 g of (R)-1,3-butanediol at each of 0, 30, and 60 minutes, culminating in a total intake of 34.5 g of (R)-1,3-butanediol. Blood BHB levels, GI tolerability, and sleepiness were assessed at baseline (0 minutes), and at 30, 60, 90, 120, 180, 240, and 300 minutes. At 240 minutes, a protein bar was consumed. The mean (±SD) BHB fasting baseline level, maximal concentration, time at maximal concentration, and incremental area under the curve over 300 minutes were 0.23 ± 0.21 mmol/L, 2.10 ± 0.97 mmol/L, 133.85 ± 57.07 minutes, and 376.73 ± 156.76 mmol/L*min, respectively. BHB levels at each time point were significantly increased relative to baseline. In females, BHB Tmax was significantly greater (p=0.046), and BHB iAUC0-300 minutes nearly significantly greater (p=0.06) than in males. The beverage formulated with Avela™ had no impact on sleepiness and was generally well-tolerated, with no or mild GI symptoms reported in most participants. Mild headaches were reported as an adverse event by five participants and judged possibly related to the study product in two of the participants.